Godzilla vs. Kong [videorecording (DVD)] - Skarsgård, Alexander; Brown, Millie Bobby, 2004-; Hall, Rebecca, 1982-; Henry, Brian Tyree (Warner Bros. Home Entertainment, 2021)
An ancient rivalry is rekindled when a Hollow Earth scholar receives private funding and wants to use Kong to discover the origin of the Titans. Protected inside a biodome since his discovery in the 70s, Kong was the only kaiju who did not participate in the epic battle against King Gidorah, and Godzilla is determined to become the final apex predator. Meanwhile, the humans begin to suspect that everyone involved is being manipulated by an industry tycoon with a vested interest in the Titans killing each other off.